2019
DOI: 10.5194/tc-2019-88
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Feature-based comparison of sea-ice deformation in lead-resolving sea-ice simulations

Abstract: Abstract. The sea-ice modelling community progresses towards Pan-Arctic simulations that explicitly resolve leads in the simulated sea-ice cover. Evaluating these simulations against observations poses new challenges. A new feature-based evaluation of simulated deformation fields is introduced and the results are compared to a scaling analysis of sea ice deformation. Leads and pressure ridges – here combined into Linear Kinematic Features (LKF) – are detected and tracked automatically from deformation and drif… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 49 publications
2
12
0
Order By: Relevance
“…We show here that the spatial scaling of sea ice deformation simulated in a realistic setup by neXtSIM holds down to the nominal resolution of the mesh, a result that is in agreement with previous analyses of the MEB model in idealized simulations (Dansereau et al, 2016) and realistic ones (Rampal et al, 2016). It means that neXtSIM does not need to be run at higher spatial resolution in order to reproduce the observed scalings, as, e.g., Hutter et al (2018) do when running at about 1 km resolution in order to resolve sea ice deformation at scale of about 10 km. Localizing the deformation at the nominal model resolution also means that related quantities, such as ridges, leads and linear kinematic features, are better resolved, although this is not investigated directly here.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We show here that the spatial scaling of sea ice deformation simulated in a realistic setup by neXtSIM holds down to the nominal resolution of the mesh, a result that is in agreement with previous analyses of the MEB model in idealized simulations (Dansereau et al, 2016) and realistic ones (Rampal et al, 2016). It means that neXtSIM does not need to be run at higher spatial resolution in order to reproduce the observed scalings, as, e.g., Hutter et al (2018) do when running at about 1 km resolution in order to resolve sea ice deformation at scale of about 10 km. Localizing the deformation at the nominal model resolution also means that related quantities, such as ridges, leads and linear kinematic features, are better resolved, although this is not investigated directly here.…”
Section: Discussionsupporting
confidence: 88%
“…Spreen et al (2017) and Bouchat and Tremblay (2017) have used scaling analysis to investigate their respective viscous plastic models, without going into the full details of a multi-fractal analysis or considering the temporal scaling. Hutter et al (2018), on the other hand, did a full multi-fractal analysis of the spatial and temporal scaling in a viscous plastic model. Their work shows that with a model running at ∼ 1 km resolution, they can reproduce reasonably good spatial scaling and multi-fractality down to the 10 km scale and up to 200 km; it is not shown how well the scaling holds down to the actual model resolution, and their spatial scaling does not hold beyond the 200 km scale.…”
Section: Introductionmentioning
confidence: 99%
“…We now investigate the sensitivity of the deformation metrics (i.e., PDFs, spatiotemporal scaling, coupling, and structure functions) to the preprocessing method used to generate a regular 3‐day deformation field. To this end, we compare the deformation statistics for the RGPS deformation fields obtained using the Weighted‐Average preprocessing method (Hutter & Losch, 2019) and using a linear interpolation of the RGPS Lagrangian positions to regular 3‐day intervals (i.e., LinInterp data set‐ Hutchings et al., 2011; Itkin et al., 2017; Lindsay & Stern, 2003). Note that the time records of the LinInterp data set always have nonzero interpolated values for the whole January–March period, while the Weighted‐Average data set may have empty records due to insufficient coverage of the original data and our choice of time constraints to construct the data set (see section 3.2).…”
Section: Resultsmentioning
confidence: 99%
“…Here, we also showed that the deformation statistics are sensitive to the preprocessing method. To do so, we compared the deformation statistics obtained using two different preprocessing methods on the RGPS Lagrangian trajectories used in previous studies: (i) the Weighted‐Average method proposed by Hutter and Losch (2019) and (ii) a linear interpolation of the trajectories in time ( LinInterp method) as in, for example, Lindsay and Stern (2003), Hutchings et al. (2011), and Itkin et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation